2015
DOI: 10.1016/j.athoracsur.2015.04.138
|View full text |Cite
|
Sign up to set email alerts
|

Tracheoplasty With Use of an Intercostal Muscle Flap for Caustic Necrosis

Abstract: We report a case of intercostal muscle flap used in tracheobronchial reconstruction for extensive necrosis after burn lesions of the posterior wall. A 32-year-old man attempted suicide by ingestion of caustic material. He underwent emergency total esogastrectomy, tracheostomy, and feeding jejunostomy. Ten days later, endoscopy showed complete destruction of the membranous trachea, extending from the tracheostomy to the carina. Reconstruction was conducted with the patient under venovenous extracorporeal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Six patients (54%) developed postoperative esophageal stricture, but all patients were able to take some or full oral nutrition (Lobeck et al 2016). Naamee et al (2015) reported the case of a 32-year-old male who underwent emergent total esogastrectomy, tracheostomy, and feeding jejunostomy following ingestion of a corrosive chemical substance. Ten days postoperative, bronchoscopy revealed complete tracheal mucosal destruction, extending from the tracheostomy to the carina.…”
Section: Surgical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six patients (54%) developed postoperative esophageal stricture, but all patients were able to take some or full oral nutrition (Lobeck et al 2016). Naamee et al (2015) reported the case of a 32-year-old male who underwent emergent total esogastrectomy, tracheostomy, and feeding jejunostomy following ingestion of a corrosive chemical substance. Ten days postoperative, bronchoscopy revealed complete tracheal mucosal destruction, extending from the tracheostomy to the carina.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Under venovenous extracorporeal; membrane oxygenation, tracheal reconstruction was performed using a pedicled intercostal muscle flap. A flap biopsy specimen obtained 7 months postoperatively revealed ciliated neoepithelium (Naamee et al 2015). Ananthakrishnan et al (2014) reported a series of 105 patients with corrosive substance ingestions treated surgically with esophageal bypass without resection of the damaged esophagus between 1977 and 2008, noting that ingestion of acidic substances was the most common (70% of patients).…”
Section: Surgical Interventionsmentioning
confidence: 99%